Solitary Rectal Ulcer Syndrome Presenting with Rectal Prolapse, Severe Mucorrhea and Eroded Polypoid Hyperplasia: Case Report and Review of the Literature - Deepak V Gopal; Christopher Young; Ronald M Katon (Canadian Journal of Gastroenterology)
A case of solitary rectal ulcer syndrome in a 36-year-old woman presenting with severe, persistent mucorrhea and eroded polypoid hyperplasia as the predominant clinical features, who was ultimately noted to have symptoms of rectal prolapse, is presented. Endoscopically, she had multiple (50 to 60) small, whitish polypoid lesions in the rectum that were initially misinterpreted as being a carpeted villous adenoma, juvenile polyposis or atypical proctitis. The lesions were treated with argon plasma coagulation with resolution, but a solitary rectal ulcer developed. The patient then admitted to a history of massive rectal prolapse over the preceding six months and underwent surgical treatment. Severe mucorrhea as the presenting feature and the presence of multiple polypoid lesions consistent with a histological diagnosis of eroded polypoid hyperplasia make the present case unique.